Вплив шунгіту на стабільність хромосом Allium fistulosum L - Городна, О.В.; Олефіренко, В.В. (Фактори експериментальної еволюції організмів, 2015)
Aims. Shungite is a mineral, medicinal properties of which are widely advertised, but the real impact on the organisms leaves unknown. The aim of our study was to investigate the effect of shungite on the chromosomes stability of Allium fistulosum. Methods. To assess genomic instability the Allium-test was used. We had counted the frequency of chromosome damages at stages of anaphase and early telophase in the apical meristem of Allium fistulosum. Results. The frequency of aberrant anaphases in the experiment was significantly lower than in controls. Germination of seeds in the experiment and control differed insignificant. Conclusions. Thus, a natural mineral shungite changes the water quality after three days of incubation. A significant decrease of frequency of aberrant anaphases was found in the study of this water impact on chromosomes. We have concluded, that shungite-incubated water positively affects on stability of the genome.